Multicentre Trials on Standardised Quantitative Imaging and Dosimetry for Radionuclide Therapies. Issue 2 (February 2021) - Lassmann, M.; Eberlein, U.; Tran-Gia, J.
Abstract: The aim of this review is to summarise the efforts undertaken so far to compare or standardise quantitative imaging with gamma cameras across centres for multicentre trials in radionuclide therapies. Overall, 10 studies were identified, five of which were set up as a multicentre effort for standardising and comparing methods for quantitative imaging. One study used positron emission tomography imaging with 124 I. In the remaining studies, measurements were carried out with planar imaging, single photon emission computed tomography/computed tomography (SPECT/CT) or a combination of both. Three studies used radioactive calibration sources that were traceable to national standards. Most of the studies were set up in the framework of multicentre clinical trials in an effort to obtain comparable quantification across sites. The use of state-of-the-art SPECT/CT systems and reconstructions has emerged as the method of choice for dosimetry in clinical trials for radionuclide therapies.